2017
DOI: 10.5888/pcd14.170268
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Consumption of Sugar-Sweetened Beverages and Sociodemographic Characteristics Among Mississippi Adults

Abstract: IntroductionThe consumption of sugar-sweetened beverages (SSBs) is linked to excessive weight gain, diabetes, and risk of cardiovascular disease. We examined the association between SSB consumption and sociodemographic characteristics among Mississippi adults.MethodsWe used data from the 2012 Mississippi Behavioral Risk Factor Surveillance System, which collected information on SSB consumption from 7,485 respondents. We used logistic regression models to calculate adjusted prevalence ratios (APRs) and 95% conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
17
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 21 publications
8
17
1
Order By: Relevance
“…Income, country of birth and marital status were found to be predictive of SSB consumption. Our finding that having a lower income predicts higher SSB consumption is consistent with past research [24, 25, 33], however studies have not previously identified country of birth and marital status as correlates of SSB consumption. This is likely due to these factors not being considered as potential correlates in previous studies [24, 25, 33].…”
Section: Discussionsupporting
confidence: 92%
“…Income, country of birth and marital status were found to be predictive of SSB consumption. Our finding that having a lower income predicts higher SSB consumption is consistent with past research [24, 25, 33], however studies have not previously identified country of birth and marital status as correlates of SSB consumption. This is likely due to these factors not being considered as potential correlates in previous studies [24, 25, 33].…”
Section: Discussionsupporting
confidence: 92%
“…and sugar sweetened beverages [38][39][40][41], the consumer group used for this study consisted of young adults.…”
Section: Experimental Designmentioning
confidence: 99%
“…Most recently, Dinnella et al [57] among other things investigated the effect of individual differences on rated sweetness intensity of an aqueous 20% w/w sucrose solution among 1119 subjects. They found that neither fungiform papillae density, gender, nor age class (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45), and 46-60-year-olds) significantly affected the rated sweetness intensity of the aqueous solution in either 6-n-propylthiouracil (PROP) non-tasters or super-tasters. Besides differences in the age classes investigated, the different result from this study might also be due to the different sucrose concentrations used.…”
Section: Effect Of Age On Ratings Of Sweet Aroma and Sweet Taste Intementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in the Jackson Heart Study cohort, mean systolic blood pressure and diastolic blood pressure levels increased with age [ 13 ], and obesity is associated increased incidence of hypertension [ 14 ]. The higher likelihood of hypertension among these subgroups may be partially due to an increasing proportion of Mississippi adults in the two highest-risk BMI categories (obesity, BMI ≥30; extreme obesity, BMI ≥40) [ 15 ] and a disproportionately higher prevalence of hypertension risk factors (e.g., physical inactivity and diabetes) among these groups [ 1 ]. In 2017, among Mississippi adults, diabetes prevalence was 13.3% for whites and 16.0% for blacks and 1.3% among those aged 18–24 years and 25.0% among those aged 55–64 years [ 16 ].…”
Section: Discussionmentioning
confidence: 99%